Analisis Kualitas Pelayanan, Kualitas Produk, dan Harga pada Loyalitas Konsumen Nano Store - Chaniago, Harmon (International Journal Administration, Business & Organization, 2020)
This study aims to analyze the factors that influence nano store customer loyalty in a small and densely populated city, namely Cimahi City, Indonesia. Respondents come from nano store consumers. The total sample of the study was 130 respondents. This research used a quantitative descriptive method and the data were analyzed by multiple regression. The results showed that simultaneously service quality, product quality, and price affect consumer loyalty. However, partial testing only affects service quality and product quality that affects customer loyalty. Meanwhile, price is not proven to be influential in increasing customer loyalty. This indicates that consumers are more focused on paying attention to product quality and service quality when shopping at nano stores.